Optimizing the methods of biathlete shooting training by means of «aiming-off» with usage of «SCATT» marksmanship trainer - Roman Zubrilov; Nikolai Astafev (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the improvement of algorithm of biathlete shooting training by means of «aiming-off» during changing wind conditions that had been earlier developed by the authors. Material & Methods: theoretical methods of scientific cognition and practical experimental training with utilization of marksmanship trainers were used. Results: correction tables of hold-off during shooting under the conditions of different strength and direction of wind were developed. Elaborated algorithm of biathlete shooting training during changing wind conditions by means of «aiming-off» was optimized and divided into four stages: the objective of the first stage was to make the athlete determine the direction of hit deviation (target impact point) from the target centre at the given mutually arranged aiming devices; that of the second stage consisted in shooting training with aiming at the given target points; that of the third stage was to teach shooting at voluntary target points in playing form, and that of the fourth stage was to neutralize the interference of conventional wind. The complex of preliminary exercises providing accelerated training of «aiming-off» was presented. Conclusions: suggested algorithm of training with usage of marksmanship trainer permits to reduce the cartridge expenditure significantly and accelerates mastering the shooting technique by biathletes under the real conditions.